Mosquitocidal efficacy of lecithinase derived from entomopathogenic bacteria Xenorhabdus sp. strain PBU1755 against filarial vector Culex quinquefasciatus. (January 2019) - Sheetal, B. Pavithra; Geetha, P.; Vaidehi, D.; Bharathi, Devaraj
Abstract: The present study describes the mosquitocidal efficacy of partially purified lecithinase enzyme against filarial vector Culex quinquefasciatus . Entomopathogenic bacteria Xenorhabdus sp. PBU1755 was isolated from entomopathogenic nematode Steinernema sp. and identified using 16S rRNA gene sequencing. The ability of lecithinase enzyme production was screened using egg yolk emulsion agar media. The enzyme production was carried out using shake flask method and the activity was optimized with different temperature, and pH. The produced lecithinase enzyme was partially purified using trichloroacetic acid (TCA) precipitation method followed by dialysis. The molecular weight of the partially purified lecithinase enzyme was determined to be ~ 70 kDa by SDS-PAGE analysis and further partially purified lecithinase enzyme activity was evaluated using zymogram assay. In addition, mosquitocidal activity of partially purified enzyme was determined against Culex quinquefasciatus . Partially purified lecithinase enzyme showed significant mosquitocidal killing efficacy and their LC50 value was estimated to be 6.77 mg. Collectively our finding suggests that the entomopathogenic bacterial enzymatic product might be used as a potential mosquitocidal agent in pest control industries. Highlights: An exo-lecithinase enzyme was partially purified from entomopathogenic bacteria Xenorhabdus sp. PBU1755 for the first time. Lecithinase showed optimum activity at pH 7.0 and 24 °C. The molecular weight of partially purified lecithinase was ~ 70 kDa on SDS-PAGE. Lecithinase showed significant mosquitocidal activity against C. quinquefasciatus .